2018
DOI: 10.1111/and.12974
|View full text |Cite
|
Sign up to set email alerts
|

Differential research of inflammatory and related mediators in BPH, histological prostatitis and PCa

Abstract: Prostate cancer (PCa) is one of the most common male malignancies in the world. It was aimed to investigate differential expression of inflammatory and related factors in benign prostatic hyperplasia (BPH), prostate cancer (PCa), histological prostatitis (HP) and explore the role of Inducible nitric oxide synthase (iNOS), (VEGF) Vascular endothelial growth factor, androgen receptor (AR) and IL-2, IL-8 and TNF-α in the occurrence and development of prostate cancer. RT-PCR was used to detect the mRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Diagnostic performances therefore not only suffer from the natural patient variability on imaging, but also from the variability in observer experience, training and capabilities [1] . Recent advances in artificial intelligence (AI), and more specifically in machine and deep learning technology, enable computer-aided diagnosis (CAD), where computer algorithms support or perform part of the image interpretation [2,3] . This is especially useful in multiparametric imaging, in which multiple modalities or techniques are combined to make the final diagnosis [4] .…”
Section: Computer-aided Diagnosis and Prostate Cancermentioning
confidence: 99%
“…Diagnostic performances therefore not only suffer from the natural patient variability on imaging, but also from the variability in observer experience, training and capabilities [1] . Recent advances in artificial intelligence (AI), and more specifically in machine and deep learning technology, enable computer-aided diagnosis (CAD), where computer algorithms support or perform part of the image interpretation [2,3] . This is especially useful in multiparametric imaging, in which multiple modalities or techniques are combined to make the final diagnosis [4] .…”
Section: Computer-aided Diagnosis and Prostate Cancermentioning
confidence: 99%
“…The rate of PC incidence reduces after controlling HI with anti-inflammatory agents, which further supports the close relationship between HI and PC development [4,14]. A recent study showed that mRNA and protein expression levels of inflammatory factors, such as inducible nitric oxide synthase, vascular endothelial growth factor, interleukin-2 and -8, and tumour necrosis factor α, were significantly increased in PC, as well as in the benign prostatic hyperplasia+prostatitis group compared to the benign prostatic hyperplasia group (p < 0.05) [11]. Vasavada et al [14] performed a meta-analysis including 20,585 subjects and 6,641 PC cases and demonstrated that HI on TRUS-Bx was associated with lower PC risk, which was similar to the findings of this study.…”
Section: Discussionmentioning
confidence: 53%
“…The specificity of PI-RADS v2/PA PI-RADS v2 was relatively low in this study, which may be due to the small sample size of benign lesions in PZ and false positive enhancement in benign lesions including prostatitis, hyperplasia, and intraepithelial neoplasia [23][24][25]. Although the inter-reader reproducibility of DCE in PZ was better in our research than in the literature [26], the rate of misdiagnosis due to DCE was still high, which implies that the two radiologists still had problems in differentiating benign and malignant lesions.…”
Section: Diagnostic Performance Comparison In Pzmentioning
confidence: 67%